FIQIH INDONESIA (Kajian Metodologis) - Jaenal Arifin (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2013)
Ideas and or motions to formulate Indonesian fiqh or Islamic law has been initiated along with the renewal of Islamic thought as a whole. However, so far a relatively thorough attention and partial toward the trend of thought of law reform mostly is approached in partial. While the review of the renewal of Islamic thought that have been done by a lot of scholars, both Indonesian and foreigners, relatively flourish. There are many thinkers and observers who are concerned about this issue, ideas that they developed at first did not get a response, after a long struggle and cultivation by scholars and ulama, finally got attention. Islamic law however does not congruent with Shari'ah. The phrase al-Syarai 'wa al-waqai mutahaddidah' mutajaddidah (Shari'ah is limited and events will always be new), suggests that if Islamic law is expected to respond with all the impact of modernization, the reinterpretation and reformulation are unavoidable.Keyword : Fiqh, Islamic Law